Scientific style and format (Univ. Press, 1994)
Covering the physical sciences and mathematics as well as the life sciences.
5. Aufl. u.d.T.: Council of Biology Editors / Style Manual Committee: CBE style manual
Keywords: Written communication; Biologie; Editoração (padrões); Escrita; Redação; Rédaction technique; Schrijfvaardigheid; Texto (editoração); Uitgeven; Wetenschappelijke publicaties; Naturwissenschaft; Science; Technical writing; Writing